A new species of Pentagramma Van Duzee (Hemiptera: Delphacidae: Asiracinae) from Chile, with notes on the host relations of the Idiosystatini Emeljanov - Campodonico, Juan F. (Zootaxa, 2017)
Pentagramma lueri sp. nov. is described from central Chile, being the first record of the genus in the country. The host relation of tribe Idiosystatini Emeljanov is discussed; indirect evidence suggests that all genera of the tribe feed on Cyperaceae.